Optical coherence tomography angiography of flat irregular pigment epithelial detachments in central serous chorioretinopathy. Issue 2 (7th April 2020) - Liu, Tingting; Lin, Wei; Zhou, Shuping; Meng, Xiangjuan
Abstract : Background: To identify and analyse the character and relationship between flat irregular pigment epithelial detachment feature (FIPED), choroidal thickness and choroidal neovascularisation (CNV) network seen on optical coherence tomography angiography (OCTA) in eyes with central serous chorioretinopathy (CSCR) in Chinese patients. Method: In the present study, 152 eyes of 144 Chinese patients, who were previously diagnosed with CSCR, were retrospectively studied. Patients' baseline characteristics, the course of CSCR, best-corrected visual acuity, the pattern of CNV on OCTA, FIPED and choroidal thickness detected by enhanced depth imaging-OCT (EDI-OCT) were analysed. Results: It was disclosed that 7.23% of CSCR patients had CNV. Age and the course of CSCR were found to be correlated with the occurrence of CNV. Among the eyes with CNV network (11 eyes), 100% of them had FIPED, whereas, among the eyes without CNV (141 eyes), 18.04% had FIPED. The maximum width and en-face area of PED were greater in the CNV group compared with that in the non-CNV group (p<0.001). It also was revealed that female gender and a poor vision were risk factors for CNV in eyes with CSCR. The choroidal thickness detected by EDI-OCT was also statistically significant between eyes with CNV and eyes without CNV. The patients who have CNV complicated with FIPED are susceptible to have low vision. Conclusion: The present research demonstrated that the majority of CNV cases were linked to FIPED, and the thinner thickness of choroid. The greater width and en-face area of PED may point towards the presence of an underlying CNV network.